Chronic inflammation within the vascular wall in pulmonary arterial hypertension: more than a spectator. Issue 5 (14th November 2019) - Huertas, Alice; Tu, Ly; Humbert, Marc; Guignabert, Christophe
Abstract: This review seeks to provide an update of preclinical findings and available clinical data on the chronic persistent inflammation and its direct role on the pulmonary arterial hypertension (PAH) progression. We reviewed the different mechanisms by which the inflammatory and immune pathways contribute to the structural and functional changes occurring in the three vascular compartments: the tunica intima, tunica media, and tunica adventitia. We also discussed how these inflammatory mediator changes may serve as a biomarker of the PAH progression and summarize unanswered questions and opportunities for future studies in this area. Graphical Abstract: